Rancangan Lereng Tambang Batu Bara Terbuka Dengan Metode Probabilistik - Frans Rezal; Muhamad Yusa; Gunawan Wibisono (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Coal was a fossil fuel. The general sense was a combustible sedimentary rock, formed from the deposition of organic matter, primarily the remains of plants and were formed through the process of coalification.One of the coal deposits was in Bangko Tengah Suban Jeriji, Muara Enim Regency, South Sumatra Province. This research examines the design of the mine pit geometry by taking into account safety andeconomic factors with probabilistic methods. The geometry of mining that was used in this design include high levels of 18 meters and a width of berm 29 meters.The result of analysis show slopes for the singleslope 1:0.50 for overburden, interburden, and underburden, 1:0.75 for seam D, and 1:1.00 for seam E. The oveall slope have a depth of 200 meters with an angle of 27o for Highwall and 12o for Lowwall. The Safetyfactor obtained in this design are 2.101 with PoF 0% for Highwall and 3.575 with PoF 0% for Lowwall. There are 4 inter-ramp on this design with safety factor 1.260, 1.569, 3.495, and 3.455. All of inter-ramphave PoF 0%. The value of the stripping ratio of this design is 12.812.Keyword: Single Slope, Overall slope, FK, PoF.